The waiting - Connelly, Michael, 1956- (Connelly, Michael, 1956- Renée Ballard and Harry Bosch novel, 2024)
"Renée Ballard and the LAPD's Open-Unsolved Unit get a hot shot DNA connection between a recently arrested man and a serial rapist and murderer who went quiet twenty years ago. The arrested man is only twenty-four, so the genetic link must be familial: His father was the Pillowcase Rapist, responsible for a five-year reign of terror in the city of angels. But when Ballard and her team move in on their suspect, they encounter a baffling web of secrets and legal hurdles. Meanwhile, Ballard's badge, gun, and ID are stolen--a theft she can't report without giving her enemies in the department ammunition to end her career as a detective. She works the burglary alone, but her mission draws her into unexpected danger. With no choice but to go outside the department for help, she knocks on the door of Harry Bosch. At the same time, Ballard takes on a new volunteer to the cold case unit: Bosch's daughter Maddie, now a patrol officer. But Maddie has an ulterior motive for getting access to the city's library of lost souls--a case that may be the most iconic in the city's history"--